The strength of trilinear higgs boson coupling in composite models - Doff, A.; Natale, A. A. [UNESP] (World Scientific Publishing, 2007)
In this work we discuss the strength of the trilinear Higgs boson coupling in composite models in a model independent way. The coupling is determined as a function of a very general ansatz for the fermionic self-energy, and turns out to be equal or smaller than the one of the Standard Model Higgs boson depending on the dynamics of the theory. © World Scientific Publishing Company.